Flow diverter stent as a definitive endovascular strategy to obliterate acute spontaneous rupture of brain aneurysmal subarachnoid hemorrhage in elderly: a case report in Indonesia - Soetanto, Gamaliel Wibowo; Usman, Fritz Sumantri (International Journal of Research in Medical Sciences, 2024)
Spontaneous rupture of brain aneurysmal subarachnoid hemorrhage (aSAH) is a debilitating disease, half of which occurs in individuals under 50 years old. Challenges in its management arise from the decision-making process regarding the preferred method of definitive aneurysm obliteration, whether through surgical intervention or endovascular approach. This study described the role of flow diverter stent as an effective endovascular approach to obliterate aSAH in the acute phase. A 70-yearold female presented with thunderclap headache, slight right hemiparesis, and pupillary-sparing left oculomotor palsy corresponding with ruptured brain aSAH. Endovascular management of flow diverter stent was preferred and inserted within the third day onset. Double antiplatelet was administered prior to and following the procedure. Three-day follow-up showed resolution of brain aSAH with no neurological sequelae. Flow diverter stent offers several advantages over coiling when treating wide-neck, giant, saccular, or fusiform aneurysm. It is also safer for elderly, especially with multiple comorbids, compared with clipping. However, it has risks of either parent/ distal artery occlusion due to its thrombogenic properties or the potential for rebleeding following dual antiplatelet administration. Effective management and thorough evaluation are essential to maximize the likelihood of favorable outcomes when employing this approach. Flow diverter stent is a promising endovascular management for ruptured brain aSAH, particularly in elderly with many comorbids and wide neck/ giant aneurysm at anterior circulation which is not candidate for coiling or clipping. It is also crucial to monitor, evaluate, and manage risk of rebleeding and thrombosis to ensure long-term success of this management approach.